Risk Factors and Clinical Aspects of Anemia in a Tertiary Care Hospital - Lahari, Samudrala; Singh, Bhanu Pratap; Laxmi, Papasani Rajya; Tharun, Bashaboina; Rao, Tadikonda Rama (Indian Journal of Pharmacy Practice)
Background: Anemia is the indicator of any related illness. More than two thirds of people have Anemia, which is frequently a sign of upcoming diseases. Identifying its clinical aspects will aim towards tailored, primary approach to treat and manage anemia. Our study aims to analyse severity of Anemia, risk factors and its impact on length of hospitalization signifying multidimensional loss of function in hospitalized patient due to Anemia. Materials and Methods: It is a prospective observational study conducted for 6 months in a tertiary care hospital among 150 patients. The data procured on various required parameters and decisive data was analysed using SPSS (IBM SPSS) version 29.0.2.0. Results: In a sample size of 150, 58% were males and 42% were females. Males were more frequent for susceptibility to every degree of anemia. Severe anemia was treated extensively whereas there is no treatment approach for any milder cases. Majority of cases had length of hospitalization for more than 15 days. Risk factors associated with anemia were Male gender (OR: 4.117), Smoking (OR: 12.304 for mild anemia and OR: 10.879 for moderate anemia) were found. Conclusion: Prevalence of anemia was found high in patients with alcoholic liver disease. Anemia prolongs hospital stays and exacerbates outcomes in patients with comorbidities. The study underscores the urgency of early intervention to treat milder cases and avert complications, given the elevated incidence of severe Anemia.
Keywords: Anemia; Risk factors; Length of hospitalization; Hemoglobin; Red Blood Cells